Metasurface-Assisted Quantum Ghost Discrimination of Polarization Objects - Vega, Andres; Pertsch, Thomas; Setzpfandt, Frank; Sukhorukov, Andrey A. (Physical Review Applied, 2021)
We develop a concept of metasurface-assisted ghost imaging for nonlocal discrimination between a set of polarization objects. The specially designed metasurfaces are incorporated in the imaging system to perform parallel state transformations in general elliptical bases of quantum-entangled or classically correlated photons. Then, only four or fewer correlation measurements between multiple metasurface outputs and a simple polarization-insensitive bucket detector after the object can allow for the identification of fully or partially transparent polarization elements and their arbitrary orientation angles. The approach can find applications for real-time and low-light imaging across diverse spectral regions in dynamic environments.
CRIS-Team Scopus Importer:2023-04-20